PENERAPAN PEMBELAJARAN BERBASIS DISCOVERY LEARNING MELALUI METODE TALKING STICK UNTUK MENINGKATKAN PEMAHAMAN KONSEP GERAK LURUS - Dani, Rahma; Latifah, Nindi Ayu; Putri, Septiona Anggela (EduFisika: Jurnal Pendidikan Fisika, 2019)
The purpose of this research is to improve the understanding of straight-motion concepts through discovery learning-based learning through the talking stick method. This research is a kind of exploratory descriptive research. The subject of the study is a student of grade X MIA 1 SMA Islam Al-Falah Jambi as many as 29 students. Data collection techniques through concept-sorting tests, student skills observation sheets and documentation. Data analysis techniques are performed in a descriptive. Learners follow the learning of discovery learning through the talking stick method of straight-motion material. Learners are enthusiastic to answer questions, brainstorm, and respond to friends ' answers. The test result of concept understanding was obtained on average 77.80. Based on the results of the study it can be concluded that discovery learning based learning through the talking stick method can improve the understanding of the straight motion concept.